Genetic Diversity Among Mycobacterium avium Subspecies Revealed by Analysis of Complete Genome Sequences - Bannantine, John P.; Conde, Cyril; Bayles, Darrell O.; Branger, Maxime; Biet, Franck (Frontiers in Microbiology, 2020)
Members of the Mycobacterium avium complex (MAC) comprise four subspecies and contain both human and veterinary pathogens. At the inception of this study, twenty-eight MAC genomes have been annotated as RefSeq genomes, facilitating direct comparisons. These genomes represent strains from around the world and provided a unique opportunity to examine genome dynamics in this complex. Each genome was confirmed to be classified correctly based on SNP genotyping and presence/absence of repetitive elements or other typing schemes. The Mycobacterium avium subspecies paratuberculosis (Map) genome size and organization was remarkably consistent, averaging 4.8 Mb with a variance of only 29.6 kb among the 13 strains. When comparing the larger genome size and variance observed among Mycobacterium avium subspecies avium (Maa) and Mycobacterium avium subspecies hominissuis (Mah) strains, this may suggest a general lack of horizontal gene transfer within the Map subspecies. Overall, MAC strains could be divided into two major sub-divisions, with the Map type II (bovine strains) clustering tightly on one end and the Mah strains clustering more loosely together on the other end. The most evolutionarily distinct Map strain was an ovine strain, designated Telford, which had >1,000 SNPs compared to the bovine type II strains. The Telford strain clustered with the Maa strains as intermediate between Map type II and Mah. SNP analysis and genome organization analyses repeatedly demonstrated the conserved nature of Map versus the mosaic nature of non-Map M. avium strains. Finally, core and pan genomes were developed for Map and non-Map strains. A total of 80% Map genes belonged to the Map core genome, while only 40% of non-Map genes belonged to the non-Map core genome. These complete genomes provide a detailed comparison of the Map, Mah and Maa strains as well as a blueprint for strains belonging to the MAC.